2023
DOI: 10.1371/journal.pone.0287117
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of altered level of blood-based biomarkers in prognosis of COVID-19 patients

Abstract: Introduction Immune and inflammatory responses developed by the patients with Coronavirus Disease 2019 (COVID-19) during rapid disease progression result in an altered level of biomarkers. Therefore, this study aimed to analyze levels of blood-based biomarkers that are significantly altered in patients with COVID–19. Methods A cross-sectional study was conducted among COVID-19 diagnosed patients admitted to the tertiary care hospital. Several biomarkers–biochemical, hematological, inflammatory, cardiac, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Results in our study showed that there was a trend increase in the tested biomarkers in all the patients. This comes in accordance with several studies that established the increase in inflammatory biomarkers in COVID-19 infection [ 7 , 14 ]. CRP, a liver-produced protein that mainly indicates an infection, inflammation, or tissue injury, was elevated in almost all patients with a mean value of 140 mg/L while its normal blood level is < 10 mg/L.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Results in our study showed that there was a trend increase in the tested biomarkers in all the patients. This comes in accordance with several studies that established the increase in inflammatory biomarkers in COVID-19 infection [ 7 , 14 ]. CRP, a liver-produced protein that mainly indicates an infection, inflammation, or tissue injury, was elevated in almost all patients with a mean value of 140 mg/L while its normal blood level is < 10 mg/L.…”
Section: Discussionsupporting
confidence: 92%
“…As the world explores the varied consequences of the pandemic, the quest for knowledge concerning COVID-19 has become essential. The interactions between SARS-CoV-2 and the diverse biochemical markers offer valuable insights into the disease’s pathogenesis and possible treatment pathways [ 7 ]. Serological tests have been used to aid in the diagnosis, prognosis, and course of treatment [ 8 ] including C-reactive protein (CRP), D-dimer, Ferritin, interleukin 6, Alanine transaminase (ALT), Aspartate transaminase (AST), and serum creatinine.…”
Section: Introductionmentioning
confidence: 99%
“…During the ongoing COVID-19 pandemic, instances of reinfection with SARS-CoV-2 have emerged, shedding light on the potential for individuals to contract the virus multiple times, often involving different viral clades or strains. This phenomenon suggests a certain level of vulnerability to reinfection, potentially from distinct genetic variants or lineages of the virus [14,15]. The evolution of SARS-CoV-2 has been marked by the emergence of various genetic mutations, leading to the development of diverse strains or variants.…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors linked to severe illness in COVID-19 include a range of elements, comprising advanced age (≥ 65 years), fertility, chronic obstructive pulmonary disease, chronic kidney conditions, diabetes mellitus, hypertension, hyperlipidemia, obesity, smoking, and immunode ciency following transplantation [7][8][9][10][11][12]. Several biomarkers, including white blood cell (WBC) count, lymphocyte count, platelet count, albumin, ALT, lactate dehydrogenase (LDH), D-dimer, ferritin, interleukin-6, procalcitonin (PCT) levels, and prothrombin time (PT), have been identi ed as speci c indicators of disease severity [13,14].…”
Section: Introductionmentioning
confidence: 99%